2018
DOI: 10.4314/jae.v22i3.9
|View full text |Cite
|
Sign up to set email alerts
|

Farmers knowledge of the role of extension services in Akwa-Ibom State Nigeria

Abstract: The study examined farmers' knowledge of the role of extension services in Akwa-Ibom State. Specifically, the study examined socioeconomic characteristics of the farmers in the study area, ascertained level of farmer's knowledge on the role of agricultural extension in general agricultural development and also identified problems militating against farmers' knowledge of these roles in the state. Multistage sampling techniques were used in selecting 180 respondents for the study. Descriptive statistics was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…From the findings therefore, it appears the extension agents did not do or are not doing enough in assisting the farmers cope or adapt their farming practices during the pandemic. This corroborates Umeh, Igwe & Anyim (2018). This may have resulted from several factors such as the extension agents themselves not being quite knowledgeable on how best to help the farmers meet the kind of needs they have or lacking the support they need in order to be able to help the farmers.…”
Section: Contributions Of Extension Agents To Farmers' Covid-19 Pande...supporting
confidence: 72%
See 1 more Smart Citation
“…From the findings therefore, it appears the extension agents did not do or are not doing enough in assisting the farmers cope or adapt their farming practices during the pandemic. This corroborates Umeh, Igwe & Anyim (2018). This may have resulted from several factors such as the extension agents themselves not being quite knowledgeable on how best to help the farmers meet the kind of needs they have or lacking the support they need in order to be able to help the farmers.…”
Section: Contributions Of Extension Agents To Farmers' Covid-19 Pande...supporting
confidence: 72%
“…The measures should ensure that the food supply chain must continue to function, the health of food system operators must be safeguarded and measures to ease the economic blow from the loss of income must be put in place. Information, advice, and coaching for rural dwellers from trusted rural communication and education institutions, such as the Agricultural Development Programme, are critical in responding to a crisis like this (Umeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These finding are also supported by Fawole & Tijani (2013) which showed high correlation between participation of farmers in extension activities and their awareness. According to (Umeh et al (2018), extension improved farmers' decision power, analytical abilities by communicating sound suggestions and information. Different extension approaches such as farmer field schools (FFS), training and visits (T&V) or participatory approach are used to share knowledge and skills with farmers (Maulu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It indicates that higher the age, education, family size, extension contact, training experience, annual family income and area under spices cultivation, lower the knowledge on spices cultivation practice. Umeh et al (2018) and Kadam (1999) found negative significant relationships between age and knowledge of the pomegranate and role of extension service, respectively.…”
Section: Ns=non-significantmentioning
confidence: 99%